Influence of a Concurrent Exercise Training Program During Pregnancy on Colostrum and Mature Human Milk Inflammatory Markers: Findings From the GESTAFIT Project. (November 2018) - Aparicio, Virginia A.; Ocón, Olga; Diaz-Castro, Javier; Acosta-Manzano, Pedro; Coll-Risco, Irene; Borges-Cósic, Milkana; Romero-Gallardo, Lidia; Moreno-Fernández, Jorge; Ochoa-Herrera, Julio J.
Background: Although exercise reduces systemic inflammation, information regarding its influence on human milk is scarce or inexistent. Research Aim: The aim of this study was to investigate the influence of an exercise intervention during pregnancy on colostrum and mature human milk inflammatory markers. Methods: The authors conducted a pseudorandomized controlled trial. The exercise group followed a concurrent aerobic and strength training, three 60-minutes sessions per week, from the 17th gestational week until delivery. For the specific aims of this study, only women able to produce enough milk were included for data analyses, resulting in 24 exercise and 23 control women. Colostrum and mature human milk proinflammatory and anti-inflammatory cytokines (fractalkine, interleukin [IL]–1β, IL-6, IL-8, IL-10, interferon [IFN]–γ, and tumor necrosis factor [TNF]–α) were measured using Luminex xMAP technology. Results: The mothers who followed the exercise program had 36% lower IL-8 and 27% lower TNF-α concentrations in their colostrum than those in the control group ( p < .05 and p < .01, respectively). The colostrum from mothers who followed the exercise program also presented borderline significant 22% lower IL-6 ( p < .100). The mature milk from mothers who followed the exercise program had 30% greater fractalkine ( p = .05) and borderline significant 20% higher IL-10 ( p = .100). The exercise intervention did not affect IFN-γ concentrations. Conclusions: This concurrent exercise program promoted a less proinflammatory profile in human milk, especially in colostrum. Moreover, it might increase mature human milk fractalkine, which could induce a greater neurodevelopment and neuroprotection in the newborn. This trial was registered at ClinicalTrials.gov (NCT02582567) on October 20, 2015.